2021
DOI: 10.1111/efp.12666
|View full text |Cite
|
Sign up to set email alerts
|

New microsatellite markers for the population studies ofRacodium therryanum, a causal agent of snow blight in Japan

Abstract: Snow mold fungi affect the seedlings of various conifer species such as spruce, fir, pine and juniper under snow (Butin, 1995;Sinclair & Lyon, 2005). The two types of snow mold diseases are snow blight and brown felt blight. The major causal agents of snow blight are Gremmenia (formerly Phacidium) abietis, G. infestans and Lophophacidium hyperboreum, which all produce annual mycelium on plant surface (Sinclair & Lyon, 2005). Those of brown felt blight are Herpotrichia juniperi and Neopeckia coulteri, which gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…We used four isolates of R. therryanum ; one was identified by Sato et al (1960) (MAFF 410406, deposited at the National Agriculture and Food Research Organization; Table 1 ) and the other three were collected from a nursery or natural forest at the University of Tokyo Hokkaido Forest (Furano, Hokkaido, Japan; Iwakiri, Sakaue, Matsushita, & Fukuda, 2021 ) or the Hokkaido University Teshio Experimental Forest (Teshio, Hokkaido, Japan). The isolates were obtained either from seedlings of two conifer species ( Picea jezoensis and Picea glehnii ) showing snow blight symptoms or from decayed seeds in Apr or May in 2009, 2018, and 2020 ( Table 1 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We used four isolates of R. therryanum ; one was identified by Sato et al (1960) (MAFF 410406, deposited at the National Agriculture and Food Research Organization; Table 1 ) and the other three were collected from a nursery or natural forest at the University of Tokyo Hokkaido Forest (Furano, Hokkaido, Japan; Iwakiri, Sakaue, Matsushita, & Fukuda, 2021 ) or the Hokkaido University Teshio Experimental Forest (Teshio, Hokkaido, Japan). The isolates were obtained either from seedlings of two conifer species ( Picea jezoensis and Picea glehnii ) showing snow blight symptoms or from decayed seeds in Apr or May in 2009, 2018, and 2020 ( Table 1 ).…”
mentioning
confidence: 99%
“…In midwestern Eurasia and North America, H. juniperi produces ascospores in summer or autumn, whereas in Japan it is always asexual and its sexual stage has not yet been found. Population genetic analyses have indicated that H. juniperi in Japan (discussed as R. therryanum ) may undergo sexual reproduction ( Iwakiri et al, 2021 ). Further studies of the life cycle of H. juniperi , especially in seasons when ascospores can be produced, are needed to elucidate differences among H. juniperi in Japan and in other regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation